THEORY AND PRACTICE OF TRANSLATION - Nazirova Diyoraxon; Ahmedov Azimjon (TADQIQOTLAR, 2025)
Thesis Summary: Translation is the process of transferring meaning from one language to another while preserving the original message, tone, and cultural context. The theory of translation focuses on the principles and strategies used to achieve accurate and meaningful translations. It includes key concepts such as equivalence, fidelity, adaptation, and the role of the translator. Translation theories are often divided into literal (word-for-word) and free (sense-for-sense) approaches. In practice, translators must consider various factors, including linguistic structure, cultural differences, and contextual meaning. The practice of translation is more than just converting words; it involves deep understanding of both source and target languages, as well as their cultures. Practical challenges include idioms, proverbs, humor, technical terms, and untranslatable concepts. Successful translation depends on the translator’s skills, knowledge, and ethical responsibility. It is both a science and an art, requiring analytical thinking and creative problem-solving. Today, the use of technology, such as CAT tools and machine translation, also plays a significant role in modern translation practice. In conclusion, the theory provides a foundation for understanding translation principles, while practice demonstrates how these principles are applied in real-world situations. Both aspects are essential for effective and professional translation.